Smartphone enabled miniaturized temperature controller platform to synthesize nio/cuo nanoparticles for electrochemical sensing and nanomicelles for ocular drug delivery applications. - Kulkarni, Madhusudan B; Velmurugan, K; Prasanth, Enaganti; Amreen, Khairunnisa; Nirmal, Jayabalan; Goel, Sanket (Biomedical Microdevices, 2021)
Undoubtedly, various kinds of nanomaterials are of great significance due to their enormous applications in diverse areas. The structure and productivity of nanomaterials are heavily dependent on the process used for their synthesis. The synthesizing process plays a vital role in shaping nanomaterials effectively for better productivity. The conventional method requires expensive and massive thermal instruments, a huge volume of reagents. This paper aims to develop an Automatic Miniaturized Temperature Controller (AMTC) device for the synthesis of nickel oxide (NiO), copper oxide (CuO) nanoparticles, and nanomicelles. The device features a low-cost, miniaturized, easy-to-operate with plug-and-play power source, precise temperature control, and geotagged real-time data logging facility for the producing nanoparticles. With a temperature accuracy of ± 2 °C, NiO and CuO nanoparticles, and nanomicelles are synthesized on AMTC device, and are subjected to different characterizations to analyze their morphological structure. The obtained mean size of NiO and CuO is 27.14 nm and 85.13 nm respectively. As a proof-of-principle, the synthesized NiO and CuO nanomaterials are validated for electrochemical sensing of dopamine, hydrazine, and uric acid. Furthermore, the study is conducted, wherein, Dexamethasone (Dex) loaded nanomicelles are developed using AMTC device and compared to the conventional thin-film hydration method. Subsequently, as a proof-of-application, the developed nanomicelles are evaluated for transcorneal penetration using exvivo goat cornea model. Ultimately, the proposed device can be utilized for performing a variety of controlled thermal reactions on a minuscule platform with an integrated and miniaturized approach for various applications.